2007
DOI: 10.1093/rpd/ncm310
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of natural radioactivity and dose rate assessment of terrestrial gamma radiation in the soil of southern Punjab, Pakistan

Abstract: Activity concentrations of (226)Ra, (232)Th, (40)K and (137)Cs in soil samples collected from the most populous area of southern Punjab of Pakistan have been measured by gamma-ray spectrometry. The measured activity concentrations for these radionuclides are compared with the reported data from different other countries and it is found that measured activity concentrations are comparable with the worldwide measured average values reported by the UNSCEAR. Subsequently assessed radiological effects show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…It may be noted that value of 226 Ra was very close to the measured world average of 50 Bq kg −1 as reported in UNSCEAR (2000). Some Pakistani areas like Lahore (Akhtar et al 2005), Punjab Province (Tahir et al 2005), and Southern Punjab (Fatima et al 2008) have lower 226 Ra levels than that of southern Rechna interfluvial region.…”
Section: Resultsmentioning
confidence: 98%
“…It may be noted that value of 226 Ra was very close to the measured world average of 50 Bq kg −1 as reported in UNSCEAR (2000). Some Pakistani areas like Lahore (Akhtar et al 2005), Punjab Province (Tahir et al 2005), and Southern Punjab (Fatima et al 2008) have lower 226 Ra levels than that of southern Rechna interfluvial region.…”
Section: Resultsmentioning
confidence: 98%
“…Harb et al (2008) in Egypt and Lu and Zhang (2008) in China have reported the natural background radiation levels about 10 times lower than the value reported in the present study. The terrestrial gamma radiation dose rate in north-west areas and Punjab province of Pakistan (0.34 and 0.28 mSv/y respectively) which were investigated by Rahman et al (2008) and Fatima et al (2008) are about one-half of the mean dose rate of Babol in the present study. (2006) from Namibia have measured the dose rate from environmental radioactivity about 45 nGy/h, 0.06 and 0.07 mSv/y respectively which are much lower than the 0.53 mSv/y in the present study especially in two latter cases.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, the current results from Arabian and Turkish coffee powders showed a mean concentration of 40 K that was higher than that obtained by Roselli et al (2013), although the mean concentration of 226 Ra was within the range found in the same study. This finding may be linked to contaminated soils in the farming areas (Fatima et al, 2008;Faanu et al, 2016 UNSCEAR (2010), all results fell below the recommended limit for the average exposure rate (84 nGy/h). External and internal hazards were also determined based on Equations 4 and 5.…”
Section: Average Annual Committed Effective Dose or Dose Ingested By mentioning
confidence: 86%